Modelling and Optimization of Fluid Frictional Torque in a Single Stage Centrifugal Pump with a Vaned Diffuser Based on RSM, ANN and Desirability Function - K. Singh; A. Singh; D. K. Singh (Journal of Applied Fluid Mechanics)
In a centrifugal pump, the clearance flow is quite common due to the existence of clearance between the casing and impeller. Apart from the clearance, the impeller speed and flow rate have a significant impact on fluid frictional torque. This study uses experimental and numerical methods to investigate these dynamics. The experimental setup includes measurements of fluid frictional torque at various levels of axial clearance (0.6 mm, 1.2 mm, and 1.8 mm), flow rates (8 L/min, 10 L/min, and 12 L/min), and impeller speeds (800 rpm, 1000 rpm, and 1200 rpm). A 3-level, 3-factor factorial design (L27) is employed to systematically examine the impact of these factors on fluid frictional torque. Response Surface Methodology (RSM) and Artificial Neural Networks (ANNs) are utilized to capture complex parameter interactions, with optimization performed using a Desirability Function (DF). The analysis reveals a significant increase in fluid frictional torque with increasing axial clearance, impeller speed, and flow rate. The optimal operational parameters for minimizing fluid frictional torque in the centrifugal pump are identified as    and mm, achieving a minimum fluid frictional torque of 0.499 Nm